2011
DOI: 10.1519/jsc.0b013e31822dfba8
|View full text |Cite
|
Sign up to set email alerts
|

How Do They Compare?: An Assessment of Predeployment Fitness in the Arizona National Guard

Abstract: Currently, there is a paucity of literature that describes physical fitness levels in deploying service members. There has been no data collected that evaluate the Army National Guard or Reserves. This descriptive study will provide physical fitness data for soldiers in the Arizona National Guard (AZNG), allowing for a comparison between the active and reserve components. Sixty soldiers from the AZNG were tested before deployment. Body composition was measured by using air displacement plethysmography. Flexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We have identified two previous studies evaluating physical demands in reserve soldiers; however, both investigated job tasks less relevant to our HG soldiers. 6,7 A few studies on fitness levels of reservists or National Guard soldiers and officers exist, [8][9][10] but these soldiers and officers are not always comparable to our HG personnel (e.g., recruited differently). Previous international studies on PA in reserve forces are also very limited, mainly presenting incomplete descriptions of self-reported PA. [9][10][11] Such PA questionnaires are often considered less valid than objective measurement techniques.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have identified two previous studies evaluating physical demands in reserve soldiers; however, both investigated job tasks less relevant to our HG soldiers. 6,7 A few studies on fitness levels of reservists or National Guard soldiers and officers exist, [8][9][10] but these soldiers and officers are not always comparable to our HG personnel (e.g., recruited differently). Previous international studies on PA in reserve forces are also very limited, mainly presenting incomplete descriptions of self-reported PA. [9][10][11] Such PA questionnaires are often considered less valid than objective measurement techniques.…”
Section: Introductionmentioning
confidence: 92%
“…12 So far, objectively measured PA has primarily been reported on full-time soldiers in small-scale studies with other research aims than reporting population values of PA. [13][14][15] Accordingly, previous international literature has recommended increased research into health, physical fitness, and readiness of reservists. 8,16 Based on the aforementioned research gaps, we initiated a study on PA and fitness levels in Norwegian HG soldiers. The fitness reference data were recently described in a separate article.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for a heighted risk of injury in part-time personnel may be lower levels of aerobic fitness in part-time personnel [9,10,11]. Part-time personnel may have a lower fitness level when compared to full time personnel, possibly due to the necessity to balance both civilian life and military life [9]. It is well known that lower aerobic fitness is a risk factor for injuries in military personnel [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated previously that part time personnel may be at greater risk of injury during combat training due to less chronic conditioning and less opportunity to be exposed to it outside of military duties 26 . Previous research has also suggested that part time personnel may be less fit than their full time colleagues 27 , increasing their risk of injury 28,29 .…”
Section: Discussionmentioning
confidence: 99%